Infecções hospitalares por micro-organismos resistentes aos antimicrobianos em pacientes internados na unidade de terapia intensiva de adultos em um hospital terciário de Minas Gerais: incidência, etiologia, fatores de risco, evolução e custos - Sabino, Sebastiana Silva (2018)
Introduction: Bloodstream infections (BI) in the Intensive Care Unit (ICU) patients represent a challenge in developing countries’ hospitals, such as Brazil, mainly because of the significant participation of antimicrobials resistant bacteria.Objectives:To analyze the incidence indicators of Infections Related to Health Care (HCAI) and ICS, their etiology, antimicrobials resistant phenotypes, risk factors, evolution and costs. Methods: A review of IRAS and sepsis cases with bacteraemia, in patients hospitalized at an adults mixed ICU at Hospital de Clínicasa t Universidade Federal de Uberlândia, was performed, from 2012 to 2014, through an active search at the Hospital Infection Control Service.We analysed 254 patients in retrospective cohort study, regarding the factors related to the hospital mortality and, a second study, case 1 (patients with infection by resistant samples) vs controls without infection; case 2 (patients with susceptible sample infection) vs controls without infection to analyze risk factors and length of hospital stay in the unit (total period and the period after the infection diagnosis). An univariate and multivariate statistical analysis was performed in relation to the second model. Additionally, these infections costs were calculated considering the extra hospitalization time (days) X the daily rate (US$;July, 2017), using the rates related to Brazil and the USA hospitals. Results: The incidence rates of infected patients and HCAI episodes were 55.1% and 91.2%, respectively; and the rate of total hospital mortality was 26.4%. Of the total of IRAs the proportion of ICS was 33.4% and the principal agent was the Coagulase-negative Staphylococcus (SCoN) 45.2%. The Gram-negative bacillus (BGNs) were responsible for 35.6% of the cases, with non-fermenting predominance (42.8%). We noticed a high frequency of microbials resistant bacteria, most notably Staphylococcus oxacillin resistant (68.8%), non-fermenting GNBs resistant to carbapenems (46.9 %) and members of the family Enterobacteriaceae resistant to broad spectrum cephalosporins (50.3%). The cohort study involving 254 patients, evidenced statistically significant mortality in critically ill patients, (ASIS ≥ 4) and more frequent when infected by gram-negative bacillus (GNBs), mixed etiology, resistant pathogens and when submitted to inappropriate treatment. The second model evidenced common predictors to both patient groups, trauma and bad prognosis (death). The extra hospitalization time of patients with ICS was 6.0 days, with no difference between those infected by resistant or susceptible samples. The total financial cost of the patients with IRAS was US$1,485.20 while on those with ICS was US$2,782.40 (US$; rates from July, 2017); the rates were defined by the Brazilian Department of Health.Conclusion:The investigation evidenced a high frequency of ICS in patients of the hospital AICU, with high epidemiological indicators in relation to the infections, aggravated by the resistant bacteria presence.The trauma as ICS predictor reflects the current situation of the hospitals ICUs in the country big cities.The implementation of effective prevention and control practices and the judicious use of antimicrobials must be the priority in the public health agenda of developing countries, considering the morbidity and mortality rates, as well as the costs evidenced in the present study.